Finite-difference approximation of first-order partial differential-functional equations - Kamont, Z. (Український математичний журнал, 1994)
We consider initial-boundary-value problems of the Dirichlet type for nonlinear equations. We give sufficient conditions of convergence of a general class of one-step difference methods. We assume that the right-hand side of the equation satisfies an estimate of Perron type with respect to the functional argument. Для нелінійних рівнянь розглядається аналог задачі Діріхле з крайовою початковою умомою. Наведені достатні умови для збіжності загального класу однокрокових різницевих методів. Припускається, що права частина рівняння задовольняє аналог оцінки Перррона відносно функції, що є аргументом.